2013
DOI: 10.3748/wjg.v19.i46.8638
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial in malignant biliary obstruction: Plasticvspartially covered metal stents

Abstract: Partially covered SEMS result in a longer duration till stent failure without increased complication rates, yet without accompanying measurable benefits in survival, performance, or quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 38 publications
0
49
1
4
Order By: Relevance
“…Egy 2013-ban Észak-Amerikában végzett összehasonlító tanulmány azonban még a koreai eredményeket is felülmúlta: SEMS esetében 55 hetes (385,3 ± 52,5 nap), míg műanyag stent esetében 21,9 hetes (153,3 ± 19,8 nap) átjárhatóságot tudtak felmutatni [12]. Ezzel éles kontrasztban 2006-ban Soderlund és mtsai Svédországban lényegesen szerényebb, SEMS esetén mindössze 14,4 hét, míg a műanyag stentek esetén 7,2 hét átlagos stentátjárhatósági időt értek el [9].…”
Section: áBraunclassified
“…Egy 2013-ban Észak-Amerikában végzett összehasonlító tanulmány azonban még a koreai eredményeket is felülmúlta: SEMS esetében 55 hetes (385,3 ± 52,5 nap), míg műanyag stent esetében 21,9 hetes (153,3 ± 19,8 nap) átjárhatóságot tudtak felmutatni [12]. Ezzel éles kontrasztban 2006-ban Soderlund és mtsai Svédországban lényegesen szerényebb, SEMS esetén mindössze 14,4 hét, míg a műanyag stentek esetén 7,2 hét átlagos stentátjárhatósági időt értek el [9].…”
Section: áBraunclassified
“…64 Furthermore, a multicenter randomized controlled trial found that SEMS had an longer patency than plastic stents. 65 This study was performed in palliative patients. However, the time to stent failure was 385 AE 52.5 days in the SEMS patients and 153.3 AE 19.8 days in the plastic stent patients.…”
Section: Stent Selection: Plastic Versus Metalmentioning
confidence: 99%
“…Com relação à sobrevida, alguns estudos indicam uma tendência de favorecimento para SEMS (Davids et al, 1992;Knyrim et al, 1993;Wagner et al, 1993;Kaassis et al, 2003;Katsinelos et al, 2006;Soderlund et al, 2006;Bernon et al, 2011;Isayama et al, 2011;Mukai et al, 2013;Walter et al, 2014) e alguns para PS (Prat et al, 1998;Moses et al, 2013), contudo esta diferença foi estatisticamente demonstrada apenas em um RCT (Sangchan et al, 2012) Neste trabalho visa-se interrogar se o que está em uso atualmente em nosso país encaixa-se nesta descrição.…”
Section: Surveillance Epidemiology and End Results (Seer) Um Banco unclassified
“…Em vista da falta de dados conclusivos sobre custo global (que inclui outros custos além do preço da prótese como, por exemplo, da internação) e do surgimento de quatro novos trabalhos não incluídos na última metanálise (Walter et al, 2014;Moses et al, 2013;Isayama et al, 2011e Bernon et al, 2011) -aumentando em cerca de 50% o número de pacientes avaliados previamente, esta revisão sistemática e metanálise tem como objetivo mostrar o desempenho de cada prótese não apenas em relação às taxas de sobrevida e de oclusão, mas abordando também questões como custos e complicações. A seguir torna-se clara e explícita a metodologia de recuperação de trabalhos assim como a sua avaliação, constando inclusive a detalhada estrutura de pesquisa por base para possibilitar reprodutibilidade caso necessária.…”
Section: Surveillance Epidemiology and End Results (Seer) Um Banco unclassified
See 1 more Smart Citation